NEW CONCEPTS REGARDING THE FUNCTIONING OF FINANCIAL SYSTEMS - MADALINA ANTOANETA RADOI (Challenges of the Knowledge Society)
On the financial market, the last three decades have gained the status of a real “revolution” as a consequence of the amplitude, transformation and restructuring of financial services and competing processes. The importance that should be paid to the transformations of financial systems is also given by their impact both at micro and macro level over economy as a whole.